Association of Sonographic Grading of Fatty Liver Disease with Liver Function Tests and CT Hounsfield: Sonographic Grading of Fatty Liver Disease with Liver Function Tests - Shahid, Muhammad Areeb; Ali, Noraiz; Yousaf, Muhammad; Fatima, Mehreen; Ahmad, Mian Hasnan; Sohail, Zainab; Niaz, Gulshan; Sohail, Areeb; Yaqoob, Namra; Khan, Sania; Tuaha Mansoor, Abdur-Rehman (Pakistan BioMedical Journal, 2022)
Fatty Liver Disease is described as the accumulation of triglycerides within cytoplasmic vesicles of hepatocytes exceeding 5 percent of total liver weight. It is generally of two types: Alcoholic or Non-alcoholic fatty liver disease. It has a tendency to progress and cause steatohepatitis, fibrosis, cryptogenic cirrhosis, hepatocellular carcinoma, chronic liver disease, metabolic syndrome, polycystic ovarian syndrome and adenocarcinomas. It is associated with obesity, diabetes mellitus, high triglycerides and low HDL levels.The Objective of this study is to find association of Sonographic Grading of Fatty Liver Disease with Liver function tests and CT Hounsfield units. The evaluation of the significance of Ultrasound and LFTs over Computed Tomography is the aim of this study for the diagnosis of Fatty Liver Disease. Material and Method:104 patients were undergone CT exams, Ultrasound exams and LFT tests for this this study (mean age: 38 years). Their hepatic (right lobe and left lobe) and Splenic Hounsfield units were obtained, Ultrasonographic grades were specified and LFTs were recorded. Crosstabulations, multiple comparisons and ANOVA was done separately on the results obtained. Results:In a cross-tabulation between Lobes of Liver, Hounsfield Units and Fatty Liver Grades through ultrasonography, a significant association is seen.The means of total bilirubin in three groups of Fatty Liver (Grade I, Grade II, Grade III) are statistically insignificant. The means of ALT, AST and Alkaline Phosphatase in three groups of Fatty Liver (Grade I, Grade II, Grade III) are statistically significant. Conclusion:It is concluded that Ultrasound is effective in diagnosing this disease in all grades of FattyLiver Disease along with Liver Function Tests.